Pergeseran Fungsi Pendidikan Islam Keluarga di Tengah Arus Modernisasi - Fadhila Najah Annisa; Puja Maharani; Sabillah Aiska; Ammar Ammar; Abdul Fadhil (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Islamic education is a fundamental aspect of child development that should primarily be instilled within the family, especially by parents. However, the rapid advancement of modernization has created increasingly complex challenges, leading to a shift in the implementation of Islamic education within the family environment. Therefore, this study aims to examine the shifts in Islamic education within families amid the growing influence of modernization. This research employed a qualitative approach using a literature review method by examining various sources, including scientific journal articles relevant to the research topic. Data were analyzed through source triangulation by comparing information obtained from multiple references, and the findings were presented descriptively. The results indicate that modernization has contributed to a shift in Islamic education by reducing family interaction and communication, making it more difficult for parents to effectively transmit Islamic values to their children. In addition, many parents tend to delegate the responsibility for religious and moral education to formal educational institutions. Consequently, the transmission of Islamic knowledge, attitudes, behavior, and moral character, which should primarily originate within the family, is not carried out optimally. These findings reflect the limited awareness of some parents regarding the importance of their role in providing Islamic education.